Studi Adsorpsi Rhodamin B Menggunakan Silika Sekam Padi - Hanif Amrulloh (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2022)
Silica was obtained from rice husk throught an extraction process and applied to remove Rhodamine B (RhB) from aqueous media by adsorption. The better characteristics of the silica were demonstrated by X-ray diffraction, N2 adsorption isotherms and scanning electron microscopy. Silica was used as adsorbent to remove RhB dye in aqueous media. Adsorption kinetics and isotherms were evaluated. Silica presented higher values of surface area, pore volume, pore diameter and porosity. Pseudo-second order was adequate to represent the kinetic profile. The adsorption isotherm follows the Langmuir and Freundlich models. Rice husk silica attained adsorption capacity of 1.06 mg g-1 coupled with removal percentage of 84%, being an excelent adsorbent for RhB dye.